Five APB UiTM Sarawak Innovative Software tested for users’ satisfaction - Ibrahim, Sueb; Francis, John (UiTM Sarawak, 2020)
Five APB UiTM Sarawak Innovative software were tested for users’ satisfaction on their multimedia elements. The multimedia elements tested in the surveys were interface, text, sound, graphic and interactivity. The software was tested out on 45 Part 1 students of UiTM Sarawak, comprising those from the Faculty of Chemical Engineering and the Faculty of Electrical Engineering. From the findings, it was revealed that the respondents were satisfied with the multimedia elements in SIR.